Knowledge Level of Citrus Grower’s Regarding use of Integrated Pest Management Strategies in Punjab - Dharamjeet Singh Grewal,; Priyanka Sharma, Tariq Iqbal, (Indian Journal of Extension Education, 2022)
The study was carried out in Punjab’s Fazilka District in 2021–2022 as it is major citrus growing district of Punjab. A total 100 respondents (citrus growers) were selected randomly from Fazilka district by using simple random sampling method. The interview schedule was prepared for collection of the data. To gauge the farmers’ level of familiarity with the various IPM tactics, a knowledge test was developed. The respondents had good educational level, bulk of the respondents fall under large category of land holding. Knowledge level of the respondents regarding Integrated Pest Management strategies found to be less. More efforts need to be done to aware the citrus growers regarding Integrated Pest Management strategies.